Flow-injection analysis coupled with electrochemical detection of poisonous inorganic arsenic(iii) species using a gold nanoparticle/carbon nanofiber/chitosan chemically modified carbon screen printed electrode in neutral pH solution - Nellaiappan, Subramanian; Pillai, K. Chandrasekara; Kumar, Annamalai Senthil (Analytical methods, 2018)
Development of simple and selective detection of poisonous arsenic species [As( iii )] in drinking water is the subject of continued research in the multi-disciplinary areas of chemistry and biology. In this paper is reported, a well dispersed gold nanoparticle decorated-carbon nanofiber-chitosan modified carbon screen printed electrode (SPE/CNF-CHIT@Au nano ) prepared using an inexpensive and simple electrochemical method for electro-catalytic oxidation and flow injection analysis (FIA) of inorganic As( iii ) species in a neutral (pH 7) phosphate buffer solution. The modified electrode has about a four times higher current signal for the arsenic oxidation than that of a gold polycrystalline electrode. The SPE/CNF-CHIT@Au nano system is highly stable in vigorously stirred solutions. Rotating disc electrode (RDE) studies performed using a glassy carbon electrode-rotating disc electrode (GCE-RDE) with its surface modified using the CNF-CHIT@Au nano film gave a heterogeneous rate constant, k cat = 1.92 × 10 4 mol −1 dm 3 s −1 for the electrochemical oxidation of As( iii ). Furthermore, SPE/CNF-CHIT@Au nano was used as an efficient electrochemical detector (ECD) for the FIA of arsenic( iii ) in a neutral pH solution. The present FIA-ECD shows zero interference with other common cationic and anionic species. As an analytical application, selective detection of As( iii ) in arsenic polluted industrial effluent and tap water samples were determined satisfactorily with good recovery values. The analysis results from FIA-ECD were comparable with those obtained using the inductively coupled plasma - optical emission spectrometry method. Simple, selective and contentious fluidic detection of As( iii ) species in drinking water has been demonstrated.